The Burkuty Plavni landmark is an oasis of the northern bryoflora in the southern steppe zone of Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2018)
The article summarizes the study of the Burkuty Plavni landmark bryoflora during period of 1983–2017. The landmark is located on the Chalbasy arena of the Nizhnodniprovski pisky in the southern steppe zone of Ukraine, 20–25 km from the Black Sea shore. The psamophytic steppes are dominat on the positive elements of the relief a meadows and wetlands with birch, alder, aspen and oak forests occupy of sand depression. These small forests are remnants of the Herodotus Gilea. The pine plantations are a main landscape elements aroud this landmark. Bryoflora includes 63 species of 36 genera of 23 families of Marchantiophyta and Bryophyta. 54 predominant Bryopsida species compose 79,38% of the bryoflora. The families Amblystegiaceae and Brachytheciaceae dominate with 9 and 8 species respectively (25,93%). Brachythecium, Sphagnum and Orthotrichum (8,1%) are main genera in bryoflora spectrum. Probably, boreal (29 species – 45,82%) and nemoral (23 species – 36,34%) mosses migrated along river valleys from the northern zones to the south. Bipolar (25 species, 39,5%) and holarctic (16, species, 25,28%) mosses migrated to Burkuty Plavni in last periods. Mesoxerophytes (20 species, 31,6%), helioscythophytes (33, 52,14%), incertophytes (52, 82,16%), oligomesotrophs and mesotrophs (18 species,56,88%), the flat surface biomorph (18 species,28,44%) and loose turf biomorph (16 species, 25,28%) were dominated. There are 31 species (49,2%) within synanthropic apophytic fraction. The greatest interest is caused by five species of the sphagnum mosses which were found in Burkuty Plavni landmark. The different points of the time and migration ways of the sphagnum mosses and other bryophytes to the south of Ukraine are discussed.
Keywords: sphagnum mosses, Chalbasy arena, Lower Dnipro sand dunes.